Reposition of Ta’zir and Ta’wid on Moral Hazard Behavior in Islamic Banking in Indonesia - Muhammad Ridha Haykal Amal; Fauzan Muhammadi (Jurnal Hukum Novelty, 2022)
Introduction to The Problem: The use of ta’zir and ta’wid in dealing with moral hazards in Islamic banking has been legalized through Bank Indonesia Regulation Number 7/46/PBI/2005 and DSN-MUI Fatwa Number 17/DSN-MUI/IX/2000. However, some scholars do not justify these policies because they are contrary to sharia rules.Purpose/Objective: This research aims to reposition ta’zir and ta’wid in dealing with moral hazard behavior. The repositioning in this context is to look for alternative ways to deal with customer moral hazard behavior.Design/Methodology/Approach: This is qualitative research involving secondary data arranged in an inductive-descriptive manner. It is also associated with a case study to obtain a complete picture of ta’zir and ta’wid in preventing moral hazards in Islamic banking. The data collected were analyzed through the stages of (1) data collection, (2) data reduction, (3) data display, and (4) conclusion/verification.Findings: Based on the results, the repositioning of ta’zir and ta’wid is necessary because, presently, its implementation contains elements of usury, which Islam forbids. Therefore, the proposed form enables customers to pay back debt in two or three installments without increasing its value in one payment. This policy enables customers whose late payment is not due to force majeure but an element of intent or bad faith.Paper Type: Research Article